Screening for depressive symptoms in postbariatric surgery patients using a validated Arabic version of Patient Health Questionnaire - Abdulmohsen F Bineid; Mustafa A Kofi; Yazieed M Albarrak; Abdulaziz M Alomaysh; Naif M Aleid (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The prevalence of depressive symptoms in obese patients is higher than nonobese patients. Evidence shows an improvement of depressive symptoms after bariatric surgery, but this improvement fluctuates 3-4 years after surgery. Some studies report a worsening of depressive symptoms, but that the type of surgery and surgical complications contribute to the high depression rate. Our objective was to assess depressive symptoms in postbariatric surgery patients using an Arabic version of Patient Health Questionnaire-9 (PHQ-9). MATERIALS AND METHODS: A cross-sectional study was conducted in a tertiary care hospital in Riyadh from January to December 2019 using a validated Arabic version of PHQ-9. The questionnaires sent through Google Survey link to patient phone numbers were registered in an electronic record system. Data analysis was analyzed using SPSS version 23. Frequency and percentages were computed for the categorical variables and mean and standard deviation were calculated for the continuous variables. Chi-square test performed to test for the association between categorical variables and depression and logistic regression analysis were performed to determine the risk factors for development of depression after bariatric surgery. RESULTS: A total of 152 patients were included in the study. Fifty percent patients did not have depression, 26.3% had mild depression, 15.8% had moderate depression, 7.2% had moderately severe depression, and only one patient (0.7%) had severe depression. Only marital status was significantly associated with depression after bariatric surgery (P = 0.019). Gender, education, marital status, and income when used in the multivariate logistic regression could not predict the incidence of depression. CONCLUSION: Using a score of 10 in PHQ-9 as a cutoff, the prevalence of depressive disorder in postbariatric surgery patients was 23.7%, which is similar to the prevalence of nonobese general Saudi population of 20%.